2020
DOI: 10.1128/msystems.00124-20
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun Metagenomics of Gut Microbiota in Humans with up to Extreme Longevity and the Increasing Role of Xenobiotic Degradation

Abstract: The gut microbiome of long-lived people display an increasing abundance of subdominant species, as well as a rearrangement in health-associated bacteria, but less is known about microbiome functions. In order to disentangle the contribution of the gut microbiome to the complex trait of human longevity, we here describe the metagenomic change of the human gut microbiome along with aging in subjects with up to extreme longevity, including centenarians (aged 99 to 104 years) and semisupercentenarians (aged 105 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 42 publications
3
77
0
Order By: Relevance
“…Moreover, the gut microbiota of people characterized by extreme longevity, i.e. semi-supercentenarians (people who reached 105 years of age), show an increased capacity of xenobiotic degradation that likely contributes to their exceptional healthy aging ( 101 ). It is becoming clear that maintaining a health-associated microbiome is crucial to successful aging.…”
Section: Role Of Microbiota and Dietary Antigens In The Development Omentioning
confidence: 99%
“…Moreover, the gut microbiota of people characterized by extreme longevity, i.e. semi-supercentenarians (people who reached 105 years of age), show an increased capacity of xenobiotic degradation that likely contributes to their exceptional healthy aging ( 101 ). It is becoming clear that maintaining a health-associated microbiome is crucial to successful aging.…”
Section: Role Of Microbiota and Dietary Antigens In The Development Omentioning
confidence: 99%
“…Another recent study [ 23 ] revealed that some beneficial gut bacteria might be lost with age. Furthermore, Rampelli’s findings [ 24 ] demonstrated that the gut microbiome of the elderly population showed a rearrangement in metabolic pathways related to carbohydrate, amino acid, and lipid metabolism. Oakley and his colleagues [ 25 ] suggested that caecal microbial communities were greatly influenced by season of outgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of ARGs in these isolated villagers implies that ARGs are inherent features of the human microbiome. Although ARGs have been implicated as the inherent features of the human microbiome, albeit excessive antibiotic administration upsurges the acquisition, transmission, and dissemination of ARGs in the gut resistomes of different hosts [ 36 ]. Moreover, the antibiotic treatment causes the modification of gut resistome thereby leading to the predominance of resistant strains and their associated ARGs [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%